Analisis Penggunaan Campur Kode Bahasa Indonesia Dan Bahasa Inggris Pada Alternative Universe “broke up(?)” KARYA @jhynjelly - Mahesa Azzahra; Trie Utari Dewi (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2023)
The problems in this research include the types and forms of code mixing in Indonesian and English on the alternative universe (AU) Twitter page on the @jhynjelly account. Alternative universe (AU) Twitter is a form of digital literary work or a type of fiction with many fans in Indonesia where the setting and situation are made different from the real life of the characters in the story. The purpose of this study is to describe the types and forms of code mixing in the Twitter alternative universe (AU) on the @jhynjelly account which tells of two people who are in a relationship who do not know each other's backgrounds, in the end they get an unexpected fate. This study applies a qualitative descriptive method. The data for this research are in the form of words, phrases and clauses which include mixing Indonesian and English codes in uploads to the Twitter account @jhynjelly. The results of this study show that there are: types of exit code mixing namely; insert code mixing (Insertion); mix code alternation (alteration); mixing code congruent lexicalization (congruent lexicalization); as well as the forms of code mixing obtained in the form of words, phrases and clauses